Chaotic grey wolf optimization algorithm for constrained optimization problems - Kohli, Mehak; Arora, Sankalap (Journal of computational design and engineering, 2018)
Graphical Abstract Graphical Abstract AbstractThe Grey Wolf Optimizer (GWO) algorithm is a novel meta-heuristic, inspired from the social hunting behavior of grey wolves. This paper introduces the chaos theory into the GWO algorithm with the aim of accelerating its global convergence speed. Firstly, detailed studies are carried out on thirteen standard constrained benchmark problems with ten different chaotic maps to find out the most efficient one. Then, the chaotic GWO is compared with the traditional GWO and some other popular meta-heuristics viz. Firefly Algorithm, Flower Pollination Algorithm and Particle Swarm Optimization algorithm. The performance of the CGWO algorithm is also validated using five constrained engineering design problems. The results showed that with an appropriate chaotic map, CGWO can clearly outperform standard GWO, with very good performance in comparison with other algorithms and in application to constrained optimization problems. Highlights Chaos has been introduced to the GWO to develop Chaotic GWO for global optimization.Ten chaotic maps have been investigated to tune the key parameter ‘a’, of GWO.Effectiveness of the algorithm is tested on many constrained benchmark functions.Results show CGWO's better performance over other nature-inspired optimization methods.The proposed CGWO is also used for some engineering design applications.